Western Biases and Assumptions as Impediments in Counselling Traditional Chinese Clients - Wong, Oye-Nam Christine; Piran, Niva (Canadian Journal of Counselling and Psychotherapy, 2007)
The paper highlights particular assumptions and biases which underlie Western approaches to counselling and offers guidelines to revising these assumptions in counselling Chinese clients. In communication styles between Chinese and Western cultures, as well as the greater emphasis within the Chinese culture on interdependence, family relations, and the community. These differences relate to varied expressions of presenting symptomatology and to communication challenges within the counselling dyad. Counsellor's familiarity with their own assumptions as well with the Chinese culture will enhance counselling interventions.